Secondary mechanisms of diversification in the human antibody repertoire - Briney, Bryan S.; Crowe, James E. (Frontiers in Immunology, 2013)
V(D)J recombination and somatic hypermutation (SHM) are the primary mechanisms for diversification of the human antibody repertoire. These mechanisms allow for rapid humoral immune responses to a wide range of pathogenic challenges. V(D)J recombination efficiently generate a virtually limitless diversity through random recombination of variable (V), diversity (D) and joining (J) genes with diverse nontemplated junctions between the selected gene segments. Following antigen stimulation, affinity maturation by SHM produces antibodies with refined specificity mediated by mutations typically focused in complementarity determining regions (CDRs), which form the bulk of the antigen recognition site. While V(D)J recombination and SHM are responsible for much of the diversity of the antibody repertoire, there are several secondary mechanisms that, while less frequent, make substantial contributions to antibody diversity including V(DD)J recombination (or D-D fusion), somatic-hypermutation-associated insertions and deletions, and affinity maturation and antigen contact by non-CDR regions of the antibody. In addition to enhanced diversity, these mechanisms allow the production of antibodies that are critical to response to a variety of viral and bacterial pathogens but that would be difficult to generate using only the primary mechanisms of diversification.